Difficulty Accessing Substance Use Treatment Among Indigenous People in a Canadian Inner City Setting - Jeffery, Tristan; Hayashi, Kanna; DeBeck, Kora; Gregg, Delilah; Milloy, MJ; Kerr, Thomas (The International Indigenous Policy Journal, 2026)
Objectives: Indigenous people in Canada continue to suffer from higher rates of opioid overdose death than non-Indigenous groups. Although substance use treatment remains a key strategy in the context of the overdose crisis, the barriers to timely substance use treatment access among Indigenous people have not been well-characterized. This study aims to identify factors affecting treatment access for Indigenous residents in Vancouver, BC.Methods: Data was derived from three prospective cohort studies of people who use drugs in Vancouver. Generalized estimating equations (GEE) were used to identify barriers to substance use treatment access among Indigenous people from June 2015 to May 2022.Results: This study included 784 Indigenous people who use drugs (median age 37.74, 48.41% who self-identified as women). At baseline, 55 (7.0%) participants reported difficulty accessing substance use treatment, increasing to 128 (16.33%) participants during follow-up. In multivariate analyses, homelessness ([AOR]: 1.63, 95% confidence interval [Cl]: 1.08 - 2.47), sex work (AOR: 1.66, 95% CI: 1.12 - 2.47), and experiencing violence (AOR: 1.87, 95% CI: 1.25 - 2.81) were positively associated with difficulty accessing treatment. In sub-analyses, participants primarily found detox programs and treatment centers to be most inaccessible, with the primary barrier being long waitlists.Discussion: The study revealed that a small, but significant, proportion of Indigenous participants, including those possessing marker of overdose risk, struggled to access treatment. These results highlight the need for specialized approaches to enhance access to culturally sensitive substance use treatment and trauma support for Indigenous individuals.